Understanding Something Means - Yepes Gonzalez, Daniela Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Daniela Alexandra Yepes Gonzalez draws us into a personal experience she had in an English practicum class, where her teacher asked her what understanding something meant. To answer the question, she turned to multiliteracies and comprehension through lived experiences. The author concludes by telling us how she has adapted these concepts in her own teaching practice.